Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Use the properties of sets to prove that for all the sets A and B, A – (A ∩ B) = A – B

Use the properties of sets to prove that for all the sets A and B, A – (A ∩ B) = A – B

Grade:12th pass

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
one year ago
Welcome to AskIITians

A – (A ∩ B) = A ∩ (A ∩ B)′ (since A – B = A ∩ B′)

= A ∩ (A′ ∪ B′) [by De Morgan’s law)

= (A∩A′) ∪ (A∩ B′) [by distributive law]

= φ ∪ (A ∩ B′)

= A ∩ B′ = A – B

Hence, proved that A – (A ∩ B) = A – B.

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free